Peningkatan Hasil Belajar Peserta Didik Pada Pembelajaran Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Team Game Tournament (Tgt) Di Kelas V - Raudhatul Jannah, Bunga; Mai Sri Lena (Jurnal Elementaria Edukasia, 2023)
More than half of students get learning outcomes under the Minimum Learning Mastery that has been set, this is due to the monotonous learning process, the lack of teacher innovation in developing learning models, and teacher-centered learning. To get optimal learning results, the cooperative learning model of the Team Game Tournament type is used which is student center, educative and fun. This study aims to describe the use of the Team Game Tournament (TGT) cooperative learning model in improving the learning outcomes of fifth grade students. This research is a Classroom Action Research consisting of two cycles. Cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. The data obtained were analyzed using qualitative and quantitative analysis. There was an increase in the lesson plan assessment, namely 87.45% in cycle I and 95.4% in cycle II. The activities of teachers and students in cycle I obtained a score of 80.3% and 73.2% respectively and scored 92.8% and 89.2% in cycle II. In integrated thematic learning, students' learning outcomes obtained a score of 72.52 in the first cycle and obtained a score of 83.19 in the cycle II.